Recent trends in cardiovascular disease deaths: a state specific perspective - Sheila M. Manemann; Yariv Gerber; Suzette J. Bielinski; Alanna M. Chamberlain; Karen L. Margolis; Susan A. Weston; Jill M. Killian; Véronique L. Roger (BMC, 2021)
Abstract Background The rate of decline in cardiovascular disease (CVD) mortality has lessened nationally. How these findings apply to specific states or causes of CVD deaths is not known. Examining these trends at the state level is important to plan local interventions. Methods We analyzed CVD mortality trends in Minnesota (MN) using the U.S. Centers for Disease Control and Prevention (CDC) Wide-ranging ONline Data for Epidemiologic Research (WONDER). Trends were analyzed by age, sex, type of CVD and location of death. Results CVD mortality rates in MN declined in 2000-2009 and then leveled off in 2010-2018, paralleling national rates. Age- and sex-adjusted CVD mortality decreased by 3.7% per year in 2000-2009 (average annual percent changes [AAPC]: -3.7; 95% CI: − 4.8, − 2.6) with no change observed in 2010-2018. Those aged 65-84 years had the most rapid early decline in CVD mortality (AAPC: -5.9, 95% CI: − 6.2, − 5.7) and had less improvement in 2010-2018 (AAPC: -1.8, 95% CI: − 2.2, − 1.5), and the younger age group (25-64 years) now experiences the most adverse trends (AAPC: 1.2, 95% CI: 0.7-1.8). Coronary heart disease (CHD) and cerebrovascular disease had the largest relative decreases in mortality in 2000-2009 (CHD AAPC: -5.2; 95% CI: − 6.5,-3.9; cerebrovascular disease AAPC: -4.4, 95% CI: − 5.2, − 3.6) with no change 2010-2018. Heart failure (HF)/cardiomyopathy followed similar trends with a 2.5% decrease (AAPC 95% CI: − 3.5, − 1.5) per year in 2000-2009 and no change in 2010-2018. Deaths from other CVD also decreased in the early time period (AAPC: -1.6, 95% CI: − 2.7, − 0.5) but increased in 2010-2018 (AAPC: 1.9, 95% CI: 0.5, 3.3). In- and out-of-hospital death rates improved in 2000-2009 with a slowing in improvement for in-hospital death and no further improvement for out-of-hospital death in 2010-2018. Conclusion Concerning CVD mortality trends occurred in MN. In the most recent decade (2010-2018) mortality from all CVD subtypes plateaued or even increased. CVD mortality among the younger age groups increased as well. These data are congruent with adverse national trends supporting their generalizability. These adverse trends underscore the urgent need for CVD prevention and treatment, as well as continued surveillance to assess progress at the state and national level.